ACADEMIC SELF-EFFICACY AND STUDENT’S ACADEMIC PERFORMANCE IN SOUTH-WEST NIGERIAN SECONDARY SCHOOLS - OLUGBENGA TIMOTHY AJADI (Innovare Journal of Social Sciences, 2025)
The scholastic achievements of secondary school students in Nigeria in externally conducted examinations, particularly the one conducted by the West African Examination Council, from 2020 to 2024 has been fluctuating and is in no way encouraging. The recurring fluctuating in performance in this computer age in public examinations has become a national issue and a significant worry for the officials in the Ministry of Education, parents, as well as other stakeholders in the education industry. Consequently, this research explored the connection between students’ belief in their academic abilities and their academic achievements in public secondary schools located in southwestern Nigeria. The population of the research focused on all students in the senior secondary class II attending public secondary schools across the six southwestern states of Nigeria, using the Research Advisor’s Table, the sample size of 384 was determined to have a 95% confidence level and a 5% margin of error. The student academic self-efficacy scale was utilized to gather information from participants. The research discovered that student academic self-efficacy has a significant relationship with student academic performance. It was recommended that secondary school principals and teachers should institute an actionable …ılution to ensure improvement and stability of student academic performance in the study area.